2012
DOI: 10.4103/0972-124x.100903
|View full text |Cite
|
Sign up to set email alerts
|

Role of antibiotics in generalized aggressive periodontitis: A review of clinical trials in humans

Abstract: Background:It is well-recognized fact that periodontal diseases are caused by multifactorial etiologies, in which microorganisms play an important role. An essential component of therapy is to eliminate or manage these pathogens. This has been traditionally accomplished through mechanical means by scaling and root planning which is ineffective in some of the aggressive periodontal diseases. These aggressive diseases involve particular groups of microorganisms which are not eliminated by mechanical means; and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Benefits of systemic administration of antimicrobial agents as adjuvant to periodontal disease treatment have been reported by numerous researchers [27][28][29][30]. The choice of antibiotics should be made after determining the susceptibility, and their administration should follow the mechanical disruption of the plaque biofilm [31].…”
Section: Resultsmentioning
confidence: 99%
“…Benefits of systemic administration of antimicrobial agents as adjuvant to periodontal disease treatment have been reported by numerous researchers [27][28][29][30]. The choice of antibiotics should be made after determining the susceptibility, and their administration should follow the mechanical disruption of the plaque biofilm [31].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 74% of the pockets with PD ≥ 5 mm at baseline were 4 mm or shallower at 6 months in the test group, compared with 54% in the control group ( p = 0.008) [ 7 ]. Additional findings supporting the use of adjunctive antibiotics with initial phase therapy are abundant, but not all studies on the topic agree that the use of systemic antibiotics makes a significant difference [ 11 , 21 ]. Varela studied the effects of AMOX + MET+ SRP compared to SRP alone for patients with GAP and found that although both groups exhibited improved parameters such as PD reductions and increased CAL, there was not a significant difference between the two therapeutic groups at 6 months [ 15 ].…”
Section: Adjunctive Antibiotic Therapymentioning
confidence: 99%
“…Antibiotics are routinely administered in conjunction with mechanical debridement to treat MIPP, effectively reducing the microbial load in periodontal pockets, particularly bacteria in the red complex and Aa [ 4 , 21 ]. Numerous studies have shown that adding antibiotics improves clinical parameters such as reduced probing depths, increased clinical attachment, and microbial population improvement in periodontal pockets [ 4 , 21 ]. The combination of AMOX + MET is the most extensively researched and evidence-based choice, with azithromycin as a viable alternative for penicillin-allergic individuals [ 9 ].…”
Section: Adjunctive Antibiotic Therapymentioning
confidence: 99%
“…However these procedures have some shortcomings like inability to reach the deep pockets and furcations (Herrera et al, 2012). Hence antimicrobials are administered along with these for complete cure of the ailment, particularly the aggressive periodontitis (Ahuja et al, 2012;Arweiler et al, 2014). The bacterial etiology of the infection should be considered before selecting an antibiotic.…”
Section: Introductionmentioning
confidence: 99%